Ross procedure versus pulmonary homograft versus mechanical valve versus bioprosthetic valve versus Ozaki procedure for surgical aortic valve replacement: a frequentist network meta-analysis - Ahmed K. Awad; Dave M. Mathew; Peter J. Fusco; Kathryn S. Varghese; Omar Abdel-Nasser; Ayman K. Awad; Peter Giannaris; Serena M. Mathew; Adham Ahmed (The Egyptian Heart Journal, 2023)
Abstract Background There has been a resurgence in interest regarding the Ross procedure due to recent publications detailing positive long-term outcomes. Conversely, surgical aortic valve replacement (SAVR) with a pulmonary homograft (PH), mechanical (MV), bioprosthetic (BV), or the Ozaki procedure each has its own technical advantages and disadvantages. Therefore, we performed a network meta-analysis (NMA) comparing other alternatives to Ross procedure. Methods Medical databases were comprehensively searched for studies comparing the Ross procedure with AVR using a PH, MV, BV, or the Ozaki procedure. Outcomes were pooled as risk ratios (RR) with their 95% confidence intervals (95% CI). Results A total of 7816 patients were pooled for our NMA from 24 studies. Compared to Ross procedure, both BV and MV were associated with significantly higher rates of 30-day mortality of RR (2.37, 95% CI 1.20–4.67) and (1.88 95% CI 1.04–3.40), respectively, with no significant difference regarding PH or Ozaki. However, only MV was associated with a higher risk of 30-day stroke (RR 8.42, 95% CI 1.57–45.23) with no significant difference in the other alternatives, as well as 30-day MI which showed no significant differences between any of the aortic conduits compared to the Ross procedure. Regarding 30-day major bleeding, MV was associated with a higher when compared to the Ross procedure RR (4.58, 95% CI 1.94–10.85), PH was associated with a lower risk of major bleeding with RR (0.35, 95% CI 0.17–0.71), and BV showed no significant difference. With a mean follow-up duration of 8.5 years compared to the Ross procedure, BV, PH, and MV were associated with a higher risk of long-term mortality with RR (1.89, 95% CI 1.38–2.58), (1.38, 95% CI 1.0–1.87), and (1.94, 95% CI 1.52–2.47), respectively, with the Ozaki procedure showed no significant difference. Regarding long-term stroke—with a mean of 6.3-year follow-up duration—there were no significant differences between any of the aortic conduits compared to the Ross procedure. Nevertheless, long-term need for reintervention—with a mean follow-up duration of 17.5 years—was significant of higher risk with both BV and PH with RR (3.28, 95% CI 1.21–8.84) and (2.42, 95% CI 1.05–5.58), respectively, compared to Ross procedure with MV and Ozaki having no significant difference. Conclusions The Ross procedure is a viable treatment option for patients undergoing SAVR, showing promising outcomes at short- and long-term follow-ups.